Surface Eddy Current Probes: Excitation Systems of the Optimal Electromagnetic Field (Review) - V. Ya. Halchenko; R. V. Trembovetskaya; V. V. Tychkov (Приборы и методы измерений, 2020)
Development of technical tools with improved metrological and operational characteristics is the actual problem of the eddy current testing. Ensuring the optimal distribution of the electromagnetic excitation field in the testing zone carries out confident detection of the defects and determination of their geometrical parameters by means of eddy current testing. The purpose of the work was to conduct an analysis of scientific and technical information in the field of eddy current testing to study of the use of electromagnetic excitation fields with a priori specified properties, as well as to generalize and systematize the accumulated experience and approaches to conduct theoretical research in this direction.A review of publications in the field of non-destructive electromagnetic testing devoted to the improvement of the excitation systems of eddy current flaw probes was carried out. The authors considered approaches in which a uniform distribution of the electromagnetic field on the control object surface was achieved by linear and non-linear optimal synthesis of excitation systems, provided the immobility of the probe relative to the testing object. Analysis of eddy current probe designs with a homogeneous excitation field created by circular, rectangular tangential and normal coils, as well as by creating a rotational excitation field was carried out. The authors studied designs of the excitation coils of probes with fields of complex configuration characterized by the original fractal geometry which can increase the probability of identifying defects that were not amenable to detection by classical probes.Studies that suggested the formation of optimal configuration fields in a given area using magnetic cores, field concentrators made of conductive materials and specially shaped screens were analyzed. The authors studied approaches to the implementation of the optimal synthesis of excitation systems of probes with uniform sensitivity in the testing zone using surrogate optimization for cases of moving testing objects taking into account the speed effect.The experience, as well as the results of theoretical studies devoted to the problem of designing eddy current probes with uniform sensitivity in the testing zone due to the uniform density distribution of the induced currents flowing in the object were generalized and systematized. As a result, the classification of probes on a number of features that characterize the excitation systems was proposed.